Effect of different types of wagon connectors on longitudinal forces of a heavy freight train - Rakshit, Utsab; Malakar, Bidhan; Krishna Roy, Binoy (International Journal of Engineering and Technology, 2018)
Indian Railway operates full rake freight trains of 2200t which consist of BOXN wagons having payload 58.08t and tare weight 23.2tfor each wagon. Longitudinal forces of a freight train have significant effects on safety parameters like derailment coefficient, comfort index and these forces are transmitted through the wagon connectors. For this reason, longitudinal forces are different for different types of wagon connectors. In this paper, the effect of different combination of wagon connectors on the longitudinal forces of a heavy freight train is studied. Nine combinations of the connectors are considered using three types of wagon connector, namely Sh-1-T, Sh-2-T, and Sh-2-V. The train model has one diesel locomotive and thirty open freight wagons each having 81.28t gross mass. The train movesona 1520mm gauge track of S-type curve having 300m radius. All simulations are performed in Universal Mechanism UM 8.1 software. The simulation results reveal that Sh-2-T wagon connector when used across the train generates the least longitudinal force.Â Â